1986
DOI: 10.1017/s0031182000049787
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Theileria parva parva infection in an endemic area of Kenya

Abstract: The maintenance of Theileria parva parva infection in an endemic area of Kenya on the shore of Lake Victoria was studied in the field and laboratory. High prevalences of antibodies against T. parva and T. mutans and intra-erythrocytic piroplasms were detected in local zebu (Bos indicus) cattle. The mean infection rate of Theileria parasites in the tick, Rhipicephalus appendiculatus, in field collections was 1.1%. Most of the infection was attributed to T. parva parva by application of field ticks to susceptibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 21 publications
1
37
0
Order By: Relevance
“…There was a low abundance of Theileria infection in H. a. anatolicum ticks collected from the field which suggests that this helps in establishing a stable enzootic condition of theleriosis and thus prevents susceptible animals from the clinical disease in the field. This feature was also observed in Rhipicephalus appendiculatus ticks infected with T. parva in Africa (Young et al 1986) and Haemaphysalis longicornis ticks infected with T. sergenti in Japan (Fujisaki and Kamio 1988;Kamio et al 1990). It was concluded that in endemic areas, ticks would usually imbibe the minimal possible dose of Theileria from cattle to maintain the infection in their salivary gland.…”
Section: Resultsmentioning
confidence: 78%
“…There was a low abundance of Theileria infection in H. a. anatolicum ticks collected from the field which suggests that this helps in establishing a stable enzootic condition of theleriosis and thus prevents susceptible animals from the clinical disease in the field. This feature was also observed in Rhipicephalus appendiculatus ticks infected with T. parva in Africa (Young et al 1986) and Haemaphysalis longicornis ticks infected with T. sergenti in Japan (Fujisaki and Kamio 1988;Kamio et al 1990). It was concluded that in endemic areas, ticks would usually imbibe the minimal possible dose of Theileria from cattle to maintain the infection in their salivary gland.…”
Section: Resultsmentioning
confidence: 78%
“…Cattle with subclinical T. parva infections become chronic carriers of piroplasms and, hence, a source of infection to the tick vector and are therefore important in the epidemiology of the disease (Young et al 1986). Modelling studies have identified the proportion of ticks infected by carrier cattle as a key factor in the transmission dynamics of T. parva (Medley et al 1993), so accurate assessment of the prevalence of carrier animals is important for a rigorous analysis of ECF epidemiology.…”
Section: Discussionmentioning
confidence: 99%
“…After an acute T. parva infection, the piroplasm parasitaemia typically drops to a very low level, although parasites are frequently still tick transmissible and the animal is termed a 'carrier', a frequent state in T. parva endemic areas in the field (Young et al 1986). Following experimental infection with T. parva Muguga, animals BT169 and BT173 were monitored over a period of 127 days, during which, sequential blood samples were collected and analysed for the presence of T. parva using p104 single primer pair PCR, p104 nPCR and RLB PCR.…”
Section: Analysis Of Persistent Infection In Cattle Experimentally Inmentioning
confidence: 99%
“…However, sterile immunity was given further credence in the late 1960s and early 1970s through the use of the T. parva Muguga stock in a very large number of experiments, once triturated tick stabilates became available (Cunningham et al 1973;Radley et al 1975;Radley 1981). This parasite, an example of the causative agent of classical ECF, does not induce carriers (Young et al 1986) and although this characteristic may be rare, it is not unique. Other stocks which might have been thought to be complex in nature, such as T. parva Pugu, which was isolated from ticks collected at a cattle holding ground near Dar es Salaam, also do not induce a carrier state (Dolan 1986a).…”
Section: Carrier States and Disease Transmissionmentioning
confidence: 99%